Bayesian Group Chain Sampling Plan Based on Beta Binomial Distribution Through Quality Region - Waqar Hafeez; Nazrina Aziz (International Journal of Supply Chain Management, 2019)
In this article, we introduced Bayesian Group Chain Sampling Plan (BGChSP) using different combination of parameters. In acceptance sampling plan, the random fluctuations can be describe in the selection of distribution Bayesian approach which is based on prior process history. We apply beta distribution as a suitable prior distribution. By considering consumer’s and producer’s risks, we consider Probabilistic and Indifference Quality Regions for the specified AQL and LQL. For the selection of parameters in BGChSP, Maximum Allowable Percent Defectives (MAPD) is also considered.